2024
DOI: 10.3390/cancers16030673
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastasis of Gastric Cancer: A Review

Itaru Yasufuku,
Hiroshi Tsuchiya,
Seito Fujibayashi
et al.

Abstract: The concept of oligometastasis is not yet fully established in the field of gastric cancer. However, metastatic lesions that are localized, technically resectable at diagnosis, present a certain response to preoperative chemotherapy, and present favorable survival outcomes with local treatments, sometimes in combination with chemotherapy, are recognized as oligometastasis in the field of gastric cancer. Oligometastasis is noted in European Society for Medical Oncology guidelines and Japanese gastric cancer tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In contrast, the AIO-FLOT3 (Arbeitsgemeinschaft Internistische Onkologie-fluorouracil, leucovorin, oxaliplatin, and docetaxel) trial revealed a good prognosis by prospectively assessing the effectiveness of multimodal treatments for GC patients with oligometastases, such as surgical excision of primary and metastatic lesions in conjunction with chemotherapy [21].…”
Section: Prognosismentioning
confidence: 99%
“…In contrast, the AIO-FLOT3 (Arbeitsgemeinschaft Internistische Onkologie-fluorouracil, leucovorin, oxaliplatin, and docetaxel) trial revealed a good prognosis by prospectively assessing the effectiveness of multimodal treatments for GC patients with oligometastases, such as surgical excision of primary and metastatic lesions in conjunction with chemotherapy [21].…”
Section: Prognosismentioning
confidence: 99%
“…Distant metastasis poses a major challenge to the long-term survival of patients with gastric cancer (GC) ( 1 , 2 ). Notably, ovarian metastasis (OM), also known as Krukenberg tumor, is one of the most common patterns of metastasis, especially in young, premenopausal female population ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis for gastric cancer with distant metastasis is poor [2], and chemotherapy with anticancer or molecular-targeted drugs is considered the mainstay of treatment [3,4]. However, recent developments in chemotherapy have had a remarkable impact on treatment strategies for unresectable metastatic gastric cancer [5].…”
Section: Introductionmentioning
confidence: 99%